Synthesis and Characterization of Silver Nanoplates by a Seed-mediated Method - Tuan Anh, Mai Ngoc; Sinh, Do Thanh; Thanh, Ngo Vo Ke; Trang, Nguyen Thi Thu; Phong, Nguyen Thi Phuong; Hai, Nguyen Dai (Communications in Physics, 2019)
Silver nanoplates (SNPs) having different size were synthesized by a seed-mediated method. The seeds -silver nanoparticles with 4 – 6 nm diameters were synthesized first by reducing silver nitrate with sodium borohydride in the present of Trisodium Citrate and Hydrogen peroxide. Then these seeds were developed by continue reducing Ag\(^+\) ions with various amount of L-Ascorbic acid to form SNPs. Our analysis showed that the concentratrion of L-Ascorbic acid, a secondary reducing agent, played an important role to form SNPs. In addition, the size and in-plane dipole plasmon resonance wavelenght of silver nanoplates were increased when the concentration of added silver nitrate increased. The characterization of SNPs were studied by UV-Vis, FE-SEM, EDS and TEM methods